The harbour of all this sea and realm : crusader to Venetian Famagusta - Walsh, Michael J. K., 1968-; Kiss, Tamás, 1976-; Coureas, Nicholas (CEU medievalia ;, 2014)
The Harbour of All This Sea and Realm offers an overview of the Lusignan, Genoese and Venetian history of the main port city of Cyprus, a Mediterranean crossroads. The essays contribute to the understanding of Famagusta's social and administrative structure, as well as the influences on its architectural, artisan, and art historical heritage from the thirteenth to sixteenth centuries. We read of crusader bishops from central France, metalworkers from Asia Minor, mercenaries from Genoa, refugees from Acre, and traders from Venice. The themes of the city's diasporas and cultural hybridity permeate and unify the essays in this collaborative effort. Some of the studies use archival sources to reconstruct the early stages of appearances of various buildings. Such research is of vital importance, given the threat to Famagusta's medieval and early modern heritage by its use as a military base since 1974.